Dimethylammonium: An A‐site Cation for Modifying CsPbI3 - Marshall, AR; Sansom, HC; McCarthy, MM; Warby, JH; Ashton, OJ; Wenger, B; Snaith, HJ (Wiley, 2020)
All‐inorganic perovskite materials are attractive alternatives to organic‐inorganic perovskites because of their potential for higher thermal stability. While CsPbI3 is compositionally stable under elevated temperatures, the cubic perovskite α‐phase is thermodynamically stable only at >330°C and the low‐temperature perovskite γ−phase is metastable and highly susceptible to non‐perovskite δ‐phase conversion in moisture. Many methods have been reported which show that incorporation of acid (aqueous HI) or “HPbI3” – recently shown to be dimethylammonium lead iodide (DMAPbI3) – lower the annealing temperature required to produce the black, perovskite phase of CsPbI3. The optical and crystallographic data presented here show that DMA can successfully incorporate as an A‐site cation to replace Cs in the CsPbI3 perovskite material. This describes the stabilization and lower phase transition temperature reported in the literature when HI or HPbI3 are used as precursors for CsPbI3. The Cs‐DMA alloy only forms a pure‐phase material up to ∽25% DMA; at higher concentrations the CsPbI3 and DMAPbI3 begin to phase segregate. These alloyed materials are more stable to moisture than neat CsPbI3, but do not represent a fully inorganic perovskite material.